2019
DOI: 10.1002/j.2334-5837.2019.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting requirements with models to improve the articulation between system engineering levels and optimize V&V practices

Abstract: Model‐based systems engineering has developed significantly over the last few years, resulting in an increased usage of models in systems specification and architecture description. The question of the positioning of requirement engineering versus MBSE is a recurrent one. This paper describes one vision of this articulation where textual and model requirements actually complete each other. The results are improved contracts across engineering levels and more formalized verification and validation practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Interestingly, recent work within the INCOSE Requirements Working Group also concludes such an information-centric approach is necessary (Wheatcraft 2019). Thales also shared similar views at the 2019 INCOSE International Symposium (Bonnet, Voirin & Navas, 2019).…”
Section: A Knowledge-enhanced Requirement Approachmentioning
confidence: 93%
“…Interestingly, recent work within the INCOSE Requirements Working Group also concludes such an information-centric approach is necessary (Wheatcraft 2019). Thales also shared similar views at the 2019 INCOSE International Symposium (Bonnet, Voirin & Navas, 2019).…”
Section: A Knowledge-enhanced Requirement Approachmentioning
confidence: 93%
“…■ Share -improve communication, reduce ambiguities and reach, as fast as possible, a common understanding of the system's purpose, form and behavior, for example, use model-based architecture views to support discussions with customers. ■ Secure -guarantee the quality of the engineering data, hopefully at any moment of the engineering process and beyond, for example, use architecture models as the backbone for textual requirements elicitation, analysis, and documentation (Bonnet 2019). ■ Automate -automate the execution of the engineering processes to improve its efficiency, through (i) automatically generating engineering artefacts from architecture models, and (ii) automate architecture tasks, for example, generate document deliverables from models, generate software modules from architecture models, and automate the exploration of solution spaces.…”
Section: Architecture Design Objectivesmentioning
confidence: 99%
“…As model-based engineering (MBSE) practices progress in being associated to requirements (Bonnet, Voirin, and Navas 2019) the definition of system in early design is improving as complexity challenges rises. The return on investment of such practices (Duffy et al 2021) has been identified.…”
Section: State Of the Art A Requirements Engineeringmentioning
confidence: 99%